THE SPECIFIC VOLUME DETERMINATION OF STATIC CONVERTERS OF THE TRACTION DRIVE WITH DC MOTORS FOR MANY SYSTEM OF ELECTRIC LOCOMOTIVES - Mukha, A. M.; Kuznetsov, O. V. (Science and Transport Progress, 2008)
The issues of determination of specific volume of static converters for multisystem railway electric rolling stock are touched on in the article.